A Study of Geometry Concept Mathematization Process on Blind Student Visual Imagery - ani, Andriy; Juniati, Dwi; Budayasa, Ketut (International Journal of Engineering and Technology, 2018)
Mathematization is organizing activities in finding regularities, relationships, and structures using first knowledge and skills. Mathematical learning classifies mathematization become horizontal mathematization and vertical mathematization. The horizontal mathematization deals with generalizing processes, while the vertical mathematization is a form of formalizing. This research analyzes geometry concept mathematization process on blind student visual imagery. This research was an exploratory study using a qualitative approach. These subjects research were one of the sixth-grade students who experienced a total blind since fifth grade from Elementary School for exceptional children in Surabaya and one of the fourth-grade student of an Elementary School for exceptional children in Sidoarjo who was totally blind by birth. The researcher interviewed and observed subjects that carried out two times by using similar problems at two different times. The subjects are assigned to explain their thinking about the definition of the angle that they recognize in their way. The blind students grapple with imaginative ideas that translated into formal definitions. Although the formal definition of the students has not entirely fulfilled their formal mathematical definition, they have been constructed the concept of the angle through mind experiments and sought to give the imagined the angle with their visual limitations.